2005
DOI: 10.21236/ada496787
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics and Prospective Environmental Sampling of Adenovirus In a Military Recruit Setting

Abstract: Background. High levels of morbidity caused by adenovirus among US military recruits have returned since the loss of adenovirus vaccines in 1999. The transmission dynamics of adenovirus have never been well understood, which complicates prevention efforts.Methods. Enrollment and end-of-study samples were obtained and active surveillance for febrile respiratory illnesses (FRIs) was performed for 341 recruits and support personnel. Environmental samples were collected simultaneously. Classic and advanced diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 9 publications
1
28
1
Order By: Relevance
“…Before vaccination was started in 1971, Ad4 and Ad7 were the major causes of ARD in basic trainees [12,47]. A true reemergence of Ad4 has been noticed in recent outbreaks of respiratory illness among recruits, with isolation rates reaching 90% and delays in training frequently being required [17,18]. The relative contribution of Ad4 to total adenovirus morbidity has steadily increased since 1996, reaching 98% of all serotyped Ad isolates in 1999 and staying at these rates through 2003 [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before vaccination was started in 1971, Ad4 and Ad7 were the major causes of ARD in basic trainees [12,47]. A true reemergence of Ad4 has been noticed in recent outbreaks of respiratory illness among recruits, with isolation rates reaching 90% and delays in training frequently being required [17,18]. The relative contribution of Ad4 to total adenovirus morbidity has steadily increased since 1996, reaching 98% of all serotyped Ad isolates in 1999 and staying at these rates through 2003 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Since the loss of the vaccine, FRI rates have more than doubled among US military recruits, and a true reemergence of Ad infections has been noted. In the absence of the vaccine, it has been estimated that 10%-20% of all military recruits become ill with a febrile Ad infection during training [17,18]. Large outbreaks of Adassociated illness have been reported in recruit training facilities nationwide, with serotypes 4 and 7 being associated with the most recently described disease epidemics [19][20][21].…”
mentioning
confidence: 99%
“…Some earlier statistical analyses have shown that marching training and firing training are significantly associated with the onset of pneumonia and FRI, especially in HAdV outbreaks [19]. During a respiratory illness outbreak in an MTC in the USA, HAdV was detected on rifle surfaces [20]. During the early period of the present outbreak, the main components of the training schedule were mid-range marches and night firing training, which may have contributed to the increased patient numbers or exacerbated their symptoms.…”
Section: Discussionmentioning
confidence: 79%
“…The report by Russell et al [1] in this issue of the Journal of Infectious Diseases is likely the most comprehensive adenovirus transmission study ever performed. Through aggressive clinical surveillance, serological assays, viral culture, frequent environmental sampling, and-most importantlyhigh-throughput molecular diagnostics, the authors clearly demonstrate the ease of respiratory virus transmission in a crowded, susceptible population.…”
mentioning
confidence: 99%
“…Hence, it seems that whether one serves as a public-health professional concerned about preventing adenovirus epidemics, a clinician concerned about protecting immunocompromised patients or preventing chronic disease, or a water-quality engineer, one needs to understand how adenoviruses interact with the environment and move from person to person. The research of Russell et al [1] serves as an excellent example in pursuing such knowledge.…”
mentioning
confidence: 99%